A Novel Skin Closure Device for Total Knee Arthroplasty: Randomized Controlled Trial versus Staples - Benner, Rodney W.; Behrens, Jonathan P. (The Journal of Knee Surgery, 2019)
Twenty-five patients undergoing simultaneous, bilateral total knee arthroplasty (TKA) were randomized to receive skin closure with Zip device on one knee and staples on the other. Patients' pain and scar appearance were rated from 0 (best) to 10 (worst). Knee arc of motion was measured by a physical therapist. At 2 weeks postoperatively, pain scores were significantly better with the Zip device during device wear (p = 0.03) and during device removal (p = 0.003); arc of motion was significantly better with the Zip device (p = 0.002). At 8 weeks of follow-up, scar appearance was significantly better in the Zip device knee as rated by the patients (1.3 vs. 2.6, p = 0.04), the surgeon (1.9 vs. 3.3, p = 0.0006), and three independent plastic surgeons (3.7 vs. 4.8, p < 0.001). Results of this randomized controlled trial show that skin closure with the Zip device resulted in less pain and better scar appearance and knee arc of motion than with staples.
Keywords: total knee arthroplasty; skin closure; cosmesis; pain rating